Caffeine analysis and extraction from a topical cream intended for UV-skin protection - Melero, Ana; Guillot, Antonio; Carneiro, Carlos; Nuñez-Sanchez, Hugo; Rodríguez-Martí, Laura; Chiari-Andréo, Bruna Galdorfini [UNESP]; Marto, Joana; Ribeiro, Helena; Garrigues, Teresa; Isaac, Vera [UNESP] (Taylor & Francis, 2020)
This study aimed to develop and validate a method for the analysis of caffeine in complex cosmetic samples, such as sunscreens. Besides, an extraction method of caffeine from coffee oil and from creams, which contains both lipophilic and hydrophilic components, has been developed. The method to analyze caffeine was developed using an isocratic pump, Waters 1515 and an automatic injector Perkin-Elmer Series 200 and an UV detector Perkin-Elmer. As stationary phase, Kromasil C-18 (150 × 4.6 mm ID with particle size of 5 µm) column was used and a mixture of water (pH 4.00)/acetonitrile (80:20, V/V) with a flow rate of 1.5 mL/min as a mobile phase. To extract the caffeine from the formulations and coffee oil, different agitation methods, solvents, and number of treatments were evaluated. The relationship between chromatographic areas and concentration of caffeine presents a linear correlation within the range 0.05–5.00 µg/mL. The precision of this method was very high, as the coefficients of variation were always lower than 6%. The DL of this technique was 3.71 ηg/mL and the QL was 11.23 ηg/mL. Three replicates of the samples obtained by the extraction method were processed obtaining a concentration of caffeine in creams between the experimental and theoretical average value of 7.48%. The literature report methodologies only in aqueous medium, different from this methodology that is fast, economical and can be used in Quality Control in the cosmetic industry. The extraction method of caffeine from matrices has also been successfully developed with absence of interferences.
Keywords: caffeine; chemical analysis; emulsion; extraction; Sunscreens